Performing the Unexpected Improvisation and Artistic Creativity - Bertinetto, Alessandro (Daimon Revista Internacional de Filosofia, 2012)
In this paper I suggest that we look to improvisation in order to understand artistic creativity. Indeed, instead of being anti-artistic in nature, due to its supposed unpreparedness, inaccuracy, and repetitive monotony, improvisation in art exemplifies and ’fuels’ artistic creativity as such. I elucidate the relationship between improvisation and artistic creativity in four steps. I discuss the concept of creativity in general (I) and in reference to art (II). Then I focus on the properties and the phenomenology of improvisation (III). Finally, I explain why improvisation can be understood as an exemplifying instance of art creativity (IV).